Failure to rescue in patients with distal pancreatectomy: a nationwide analysis of 10, 632 patients. Issue 9 (September 2021) - Lequeu, Jean-Baptiste; Cottenet, Jonathan; Facy, Olivier; Perrin, Thomas; Bernard, Alain; Quantin, Catherine
Abstract: Background: FTR appears as a major cause of postoperative mortality (POM). Hospital volume has an impact on FTR in pancreatic surgery but no study has investigated this relationship more specifically in DP. Methods: We analysed patients with DP between 2009 and 2018 through a nationwide database. FTR definition was mortality among patients who experiment major complications. The cutoff between high and low volume centers was 20 pancreatectomies per year. Results: Some 10, 632 patients underwent DP, 5048 (47.5%) were operated in 602 (95.4%) low volume centers and 5584 (52.5%) in 29 (4.6%) high volume centers. Overall FTR occurred in 11.2% of patients and was significantly reduced in high volume centers compared to low volume centers (10.2% vs 12.5%, p = 0.047). In multivariate analysis, surgery in a high volume center was a protective factor for POM (OR = 0.570, CI95% [0.505–0.643], p < 0.001) and also for FTR (OR = 0.550, CI95% [0.486–0.630], p < 0.001). Conclusion: Hospital volume has a positive impact on FTR in DP. Patients with higher risk of FTR are men, with high modified Charlson comorbidity index, malignant conditions and open procedures.